2015
DOI: 10.1016/j.crte.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and zircon U–Pb geochronology of the ultramafic and mafic rocks emplaced within the anatectic series of the Variscan Pyrenees: The example of the Gavarnie–Heas dome (France)

Abstract: International audienceThe origin and evolution of ultramafic (UM), mafic (M) and intermediate rocks emplaced within the metamorphic and anatectic series of the middle crust of the Variscan segment of the Pyrenees are defined in the light of new isotopic data U–Pb zircon ages, and Sr, Nd isotopic ratios. In the Gavarnie–Heas dome (central Pyrenees), ultramafic, mafic and intermediate rocks form three massifs several kilometers in size emplaced within the anatectic series: (i) the Gloriettes massif, which mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…For that, an additional asthenospheric heat source is required in a context of attenuated or missing lithospheric mantle (Sandiford and Powell, 1991;Chardon et al, 2009). The switch from crustal to mantle and hybrid sources of 310-290 Ma plutonism in the Pyrenees (e.g., Kilzi et al, 2016) is in agreement with such a lithospheric configuration that enhances mantle-crust interactions. This switch, which is also documented across both limbs of the syntax after ca.…”
Section: The Pyrenees Within the Closing Iberianarmorican Syntaxmentioning
confidence: 55%
See 1 more Smart Citation
“…For that, an additional asthenospheric heat source is required in a context of attenuated or missing lithospheric mantle (Sandiford and Powell, 1991;Chardon et al, 2009). The switch from crustal to mantle and hybrid sources of 310-290 Ma plutonism in the Pyrenees (e.g., Kilzi et al, 2016) is in agreement with such a lithospheric configuration that enhances mantle-crust interactions. This switch, which is also documented across both limbs of the syntax after ca.…”
Section: The Pyrenees Within the Closing Iberianarmorican Syntaxmentioning
confidence: 55%
“…2) intruding the roof of the infrastructure at 307 ± 3 Ma and 300 ± 2 Ma, and suggested that the first group dated metamorphism and the second pluton crystallization. Recently, Kilzi et al (2016) obtained an age of 294 ± 1 Ma by LA-ICPMS on zircons in a mantle-derived dioritic sill hosted by migmatites of the Gavarnie massif (Fig. 2).…”
Section: Pszmentioning
confidence: 99%
“…Up to now, only few geochronological constraints are available on migmatites, anatectic granites and mafic to intermediate magmatic bodies in the Pyrenees. Recent works suggest that magmatic activity lasted until the middle Permian (Aguilar et al, 2014;Esteban et al, 2015;Kilzi et al, 2016). We present new geochronological data on migmatites and magmatic rocks from the Lesponne and Chiroulet gneiss domes and the Neouvielle pluton, in the western Axial Zone (figure 1b).…”
Section: Introductionmentioning
confidence: 60%
“…10: Maps of Early Permian (Autunian, 290-260 Ma) sedimentary basins and volcanics compiled from Trümpy and Dösseger (1972), Lorenz and Nicholls(1976) , Feys (1989), Châteauneuf (1989), Burg et al (1994) and Cassinis et al (2012). Late Carboniferous and Early Permian gabbros and granulites exhumed by tectonic activity or Tertiary to Quaternary volcanoes are indicated with: 1 -Iberian margin (ODP Site 1069; Manatschal et al 2001); 2 -Spanish Central System (Fernández-Suárez et al 2006;Villaseca et al 2007); 3 -Gavarnie-Héas dome (Kilzi et al 2016);4 -Ursuya massif, Pyrenees (Vielzeuf 1984;Vielzeuf and Kornprobst 1984); 5 -Quérigut massif, Pyrenees (Roberts et al 2000); 6 -Treilles norite, Pyrenees (Vielzeuf and Pin 1991); 7 -Ceret gabbro, Pyrenees (Aguilar et al 2014); 8 -Calabria (Schenk 1980;Caggianelli et al 2013); 9 -Santa Lucia massif, Corsica (Paquette et al 2003;Rossi et al 2006); 10 -Bocca di Tenda gabbro, Corsica (Cocherie et al 2005;Tribuzio et al 2009); 11 -Puy Beaunit, French Massif Central (Downes et al 1991;Costa and Rey 1995;Féménias et al 2003); 12 -Bournac, French Massif Central (Rossi et al 2006); 13 -Eiffel massif, Germany (e.g. Loock et al 1990); 14 -Monte Ragola, Appenines (Meli et al 1996); 15 -Ivrea zone, Southern Alps (Pin 1986;Vavra et al 1999;Quick et al 2003;Peressini et al 2007); 16 -Sassa, Sermenza and Mont Collon, Western Alps (Bussy et al 1998;Monjoie et al 2007;…”
Section: Discussionmentioning
confidence: 99%